Effect Of Nb, Cr And W On The High Temperature Oxidation Behavior Of Ti-Al Alloys - Sapiai, Napisah (2011)

(untitled)
This research is focused on intermetallic TiAl and their oxidation behavior for structural materials at high temperatures in automotive, aerospace and gas turbine industries. However, the commercial application of Ti-Al is currently limited by their insufficient oxidation resistance at temperature above 700-850oC. The addition of alloying elements such as Nb, Cr and W is significant in producing good Ti-Al alloys for high temperature applications. Ti-Al alloys were fabricated using arc- melting furnace. Then the phases present, microstructure evaluation and hardness test were characterized using XRD, FESEM/EDX and Vikers hardness.